Phenotypic identification, nutrients content, bioactive compounds of two jengkol (Archidendron jiringa) varieties from Bengkulu, Indonesia and their potentials as ruminant feed - NUR HIDAYAH; RUKIAH LUBIS; KOMANG G WIRYAWAN; SRI SUHARTI (Society for Indonesian Biodiversity, 2019)
Abstract. Hidayah N, Lubis R, Wiryawan KG, Suharti S. 2019. Phenotypic identification, nutrients content, bioactive compounds of two jengkol (Archidendron jiringa) varieties from Bengkulu, Indonesia and their potentials as ruminant feed. Biodiversitas 20: 1671-1680. Agricultural waste is abundant in tropical countries. Many farmers in these countries have been using this waste as the main sources for feeding livestock. Ones of them are jengkol (Archidendron jiringa) by-product like peels and leaves have not been utilized optimally. The aims of this study were to explore the peel and leaves of two varieties of jengkol, i.e., jengkol gajah and jengkol padi, from Bengkulu Province and to assess their potentials as ruminant feed. Variables observed were phenotypic identification, nutrients content, and bioactive compounds. Phenotypic identification was completed using non-experimental examination through survey and observation methods to identify the phenotypic characters of jengkol in four districts in Bengkulu. The peel of jengkol padi had a blackish purple color and was thicker than that of jengkol gajah. The leaves of jengkol gajah was longer (10.2-15.5 cm), but jengkol padi had wider leaves (6-7.5 cm). The proportion of weight of jengkol peel (59.99%) is higher than seed (40.01%). Jengkol peel had high fiber content (33.07-35.28%) while the leaves were rich in protein and total digestible nutrient (TDN) (15.17-19.26% and 63.87-65.82%). In nutrient content comparison, the peel of jengkol padi was better (crude protein (CP:8.41%, ether extract (EE):0.79%, crude fiber (CF): 35.28% and total digestible nutrient (TDN): 52.81% but jengkol gajah had better nutrient in its leaves (CP:19.26%, EE:2.50%, CF:26.66% and TDN:51.56%).The saponin content (26.52%), total phenol (2.99%), and tannin (1.22%) in the peel were higher than those in the leaves, while the leaves had higher flavonoids content (2.0%) than the peels. Bioactive compounds in jengkol gajah were higher than those in jengkol padi. Based on this study, both jengkol gajah and jengkol padi are potential as ruminant feed in which the peel can be a source of fiber and saponins, while the leaves are potentially used as a source of protein, fiber and saponins.